2018
DOI: 10.3892/etm.2018.6144
|View full text |Cite
|
Sign up to set email alerts
|

Maternal lipids, BMI and IL‑17/IL‑35 imbalance in concurrent gestational diabetes mellitus and preeclampsia

Abstract: The objective of the present study was to investigate the role of blood glucose, lipid metabolism, body mass index (BMI), C-reactive protein (CRP) as well as an interleukin (IL)-17/IL-35 imbalance in the pathogenesis of concurrent gestational diabetes mellitus (GDM) and preeclampsia (PE) (DPE). The mRNA expression of forkhead box protein 3 (FoxP3), IL-35 [including Epstein-Barr virus-induced gene 3 (EBI3) and P35 subunits] and IL-17 in the peripheral blood mononuclear cells of patients with DPE (n=30), GDM (n=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 60 publications
1
41
0
Order By: Relevance
“…Our results showed that there was a weak positive correlation of serum level of IL-17 with TG and VLDL in T2DM patient and the control groups. A previous study reported that elevated serum levels of IL-17, TG, and VLDL may play a role in the development of endothelial damage and vascular dysfunction, then causing systemic inflammation and endothelial dysfunction and may be involved in the pathogenesis of DM [31].…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that there was a weak positive correlation of serum level of IL-17 with TG and VLDL in T2DM patient and the control groups. A previous study reported that elevated serum levels of IL-17, TG, and VLDL may play a role in the development of endothelial damage and vascular dysfunction, then causing systemic inflammation and endothelial dysfunction and may be involved in the pathogenesis of DM [31].…”
Section: Discussionmentioning
confidence: 99%
“…Lipid metabolism disorders begin in the early stages of the disease and play an important role in the development of metabolic diseases during pregnancy. 13,15 As the abnormal lipid metabolism can promote the incidence of GDM and/or PE, controlling blood lipids within an appropriate range may reduce the incidence of maternal complications. 16 Lysophosphatidylcholine LPC is increasingly recognized as a key factor positively associated with cardiovascular diseases.…”
Section: Figurementioning
confidence: 99%
“…Yan et al [9] demonstrated that serum and vitreous levels of IL-35 were significantly decreased in patients with proliferative diabetic retinopathy (PDR). Lower serum levels of IL-35 were also detected in patients with gestational diabetes mellitus (GDM) and preeclampsia (PE) [10]. A large quantity of evidence has revealed that IL-35 could inhibit tumor necrosis factor (TNF)-α-induced activation of nuclear factor (NF)-κB via the signal transducer and activator of transcription 1 (STAT1) phosphorylation and suppressed the phosphorylation of MAPK family including JNK, ERK, and p38 activated by lipopolysaccharide (LPS) [11, 12].…”
Section: Introductionmentioning
confidence: 99%